FLASHCARD MEDIA EFFECTIVENESS IN ENRICHING STUDENTS’ ENGLISH VOCABULARY AT VOCATIONAL SCHOOL - Bambang Nur Alamsyah Lubis; Rakhmat Wahyudin Sagala; Khairun Niswa (English Review: Journal of English Education, 2023)
This study aimed to describe the effectiveness of flashcard media in enriching student’s English vocabulary. The objective of the study referred to identify the effectiveness of flashcard media, and to evaluate flashcard media in enriching student English vocabulary. Descriptive qualitative was used as a research method. The data of this study was a result of questionnaire and interview, and the source of the data was taken from students at SMK Swasta Yapim Biru-Biru. The result of this study was that flashcard media were successfully effective in enriching students' vocabulary, and flashcard media must have more variety. For instance, the flashcard did not only show animal, school tool, and home furniture pictures; it could also show road signs, motorcycle and car spare parts, machine material, and computer material pictures, all of which were suitable for student vocational needs.Flashcard media must be appropriated to students’ needs. Its purpose, to make sure flashcard media was accepted and right on target.